Avaliação das atividades gastroprotetora, anti-Helicobacter pylori, imunomoduladora e antioxidante dos "boldos" de interesse ao SUS : Plectranthus barbatus Andrews (Lamiaceae) e Vernonia condensata Baker (Asteraceae) - Borges, Augusto Santos (2017)
Helicobacter pylori is a Gram-negative bacteria capable to survive the gastric environment and has a great influence in the development of many gastric diseases, like gastritis, peptic ulcers and even the gastric cancer. Plectranthus barbatus (Falso-boldo) and Vernonia condensata (Boldo-baiano) are species of medicinal plants with a wide traditional use in Brazil for the treatment of gastric injuries, however, none scientific reports have been described about the activity against H. pylori. Thus, this study aimed to determine the anti-H. pylori activity, gastroprotection activity, immunomodulation activity, antioxidant activity and phytochemical profile of extracts and fractions of these species. The phytochemical profile was evaluated through preliminary phytochemical assay, polyphenols and flavonoid content assays and mass spectrometry. The gastroprotective was measured by in vivo ulcer model induced by ethanol. The anti-H. pylori activity was made by minimal inhibitory and bactericidal concentration (MIC and MBC) and urease inhibition activity. The immunomodulatory activity was measured by detection of nitric oxide and cytokines (TNF-α, IL-1β and IL-6) released from LPS stimulated macrophages. Furthermore, was made the inhibitory potential against the artificial radicals (DPPH and ABTS•+) and oxygen and nitrogen reactive species (O2 - , HOCl, H2O2 and NO). The oral treatment with the extracts from both species shows gastroprotection ranging 58 – 78%. The anti-H. pylori results was significant only for the P. barbatus species, which showed an MIC of 256 µg/mL for the ethyl acetate fraction (AcOEt) and 512 µg/mL for the aqueous extract. Furthermore, the AcOEt fraction showed MBC of 1024 µg/mL. The results of the antioxidant capacity were significant for both species against the artificial radicals as well to the reactive oxygen species: O2 - (IC50: 32 – 72 µg/mL) and HOCl (IC50: 53 – 85 µg/mL). For the results of immunomodulatory activity, was possible to realize anti-inflammatory capacity in both species, but, the V. condensata showed greater potential and managed to decrease the productions of NO and cytokines, in a dose-response way, in the LPS stimulated macrophages (28 – 88 % of inhibition). Both species showed significant amounts of flavonoids and polyphenols. In addition, P. barbatus presented different diterpenes such as plectrin, hydrolyzed abietane, barbatusin, 3β- hydroxy-3deoxybarbatusin and cyclobutatusin as well the polyphenols coleoside B and rosmarinic acid. Altogether, the P. barbatus species, in special your AcOEt fraction, proved to be promising for future use in the prevention and treatment of H. pylori infections, because in addition to the inhibition of growth of H. pylori capacity, it also showed promising gastroprotective, immunomodulatory and antioxidant activity.